77 Returned Gilts and Their Subsequent Reproductive Performance on Commercial Farms. (10th April 2018) - Tani, S; Piñeiro, C; Koketsu, Y
Abstract: The objectives of this retrospective swine cohort study were 1) to characterize return occurrences in gilts, 2) to determine risk factors for a return occurrence in gilts, and 3) to compare both reproductive performance across parities and lifetime performance between returned gilts and no-return gilts. Data from farm-entry to removal included 832, 865 first service records of 160, 937 females on 155 Spanish farms, served between 2011 and 2016. Two farm categories were defined on the basis of the upper 25 th percentile of the farm means of the number of pigs weaned per sow per year: high-performing farms (> 26.2 pigs) and ordinary farms (≤ 26.2 pigs). Mixed-effects models were applied to by-parity data and lifetime data. For served gilts the mean return occurrence was 12.2%, with one, two and three or more return occurrences occurring in 9.7, 2.1 and 0.4% of gilts, respectively. Removal due to reproductive failure was done for 15.6% of returned gilts compared with only 11.2% of no-return gilts. Also, 6.3-13.3% of the returned gilts were returned again at subsequent parities, compared with only 5.8-10.5% of no-return gilts. A higher return risk for gilts was associated with summer season and being fed on ordinary farms (P < 0.05). With regard to lifetime performance, the parity at removal of returned gilts was 1.0 lower than for no-return gilts, but the returned gilts produced only 0.1 fewer lifetime pigs born alive per parity (P < 0.05). Also, there was no difference between two farm groups for parity at removal (P = 0.06; 4.5 vs. 4.7). However, returned gilts on high-performing and ordinary farms had 57.2 and 61.5 more lifetime non-productive days, respectively than no-return gilts (P < 0.05). With regard to subsequent reproductive performance, the proportion of 0-6 days of subsequent weaning-to-first-service interval across parities was 2.3-7.9% less for returned gilts than for no-return gilts (P < 0.05). In conclusion, returned gilts had lower longevity and more non-productive days than no-return gilts, but they produced similar numbers of pigs born alive per parity. Therefore, management of returned gilts is critical to reduce non-productive days.